2004
DOI: 10.1074/jbc.m406132200
|View full text |Cite
|
Sign up to set email alerts
|

Lysosome-Sarcoplasmic Reticulum Junctions

Abstract: Previous studies on pulmonary arterial smooth muscle cells have shown that nicotinic acid adenine dinucleotide phosphate (NAADP) evokes highly localized intracellular Ca 2؉ signals by mobilizing thapsigargininsensitive stores. Such localized Ca 2؉ signals may initiate global Ca 2؉ waves and contraction of the myocytes through the recruitment of ryanodine receptors on the sarcoplasmic reticulum via Ca 2؉ -induced Ca 2؉ release. Here we show that NAADP evokes localized Ca 2؉ signals by mobilizing a bafilomycin A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
123
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 182 publications
(138 citation statements)
references
References 33 publications
13
123
2
Order By: Relevance
“…2 The latter findings concur with recent reports identifying NAADP-sensitive Ca 2ϩ stores as reserve granules in sea urchin eggs (12) and secretory granules in MIN-6 cells (35,36), both acidic stores of Ca 2ϩ . NAADP may also target lysosome-related Ca 2ϩ stores in pancreatic acinar cells (36) and smooth muscle cells (37). At the cellular level, expression of NAADP receptors in cortical neurons is consistent with our previous autoradiographical analysis of NAADP binding sites in adult rat brain (38).…”
Section: Resultssupporting
confidence: 90%
“…2 The latter findings concur with recent reports identifying NAADP-sensitive Ca 2ϩ stores as reserve granules in sea urchin eggs (12) and secretory granules in MIN-6 cells (35,36), both acidic stores of Ca 2ϩ . NAADP may also target lysosome-related Ca 2ϩ stores in pancreatic acinar cells (36) and smooth muscle cells (37). At the cellular level, expression of NAADP receptors in cortical neurons is consistent with our previous autoradiographical analysis of NAADP binding sites in adult rat brain (38).…”
Section: Resultssupporting
confidence: 90%
“…This method takes advantage of the irreversible binding of NAADP to its yet uncharacterized receptor (46). With this assay, an NAADP concentration of 4 M has been determined in activated sea urchin sperms (13) as well as an increase in cellular NAADP levels upon stimulation of pancreatic beta cells with glucose (10), upon stimulation of murine pancreatic acinar cells with cholecystokinin (11), and upon stimulation of arterial smooth muscle cells with endothelin-1 (12). In addition, basal cellular concentrations of NAADP in erythrocytes (16 nM), rat hepatocytes (4.5 nM), and Escherichia coli cells (2.5 nM) have been reported (14).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore NAADP-induced Ca 2ϩ release via RyR has been described for MIN6 cells (22), pancreatic acinar cells (23,24), and human T cells (25,26). Galione and co-workers (10,12,27,28) recently reported the release of Ca 2ϩ by NAADP from a lysosomal compartment. Thus, both a "one pool-one receptor" mechanism (NAADP directly activates RyR) and a "two-pool" mechanism (NAADP releases Ca 2ϩ from a lysosomal store, which than induces Ca 2ϩ release by RyR) may be used by different cell types (for a review, see Ref.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Using isolated cells or tissues, NAADP-induced Ca 2ϩ signaling has been implicated in the regulation of several physiological functions such as egg fertilization (12,13), T lymphocyte activation (14), muscle contraction (15), and neuronal differentiation (16). The role of NAADP in vivo, however is not known, although a recent study demonstrated that a newly described NAADP antagonist could prevent T cell motility in an animal model of multiple sclerosis (17).…”
mentioning
confidence: 99%